Capital adequacy beyond Basel : banking, securities, and insurance - Scott, Hal S. (Oxford University Press, 2005)
The research contained in this book covers some key issues at stake in the capital requirements for insurance and securities firms. Contributors analyse the use of subordinated debt, internal models, and rating agencies in addition to examining the effect on capital of reinsurance and similar instruments.